IBM Pemberdayaan Kader Kesehatan dalam Pencegahan Terjadinya Anemia Ibu Hamil - Yuni Astuti; Tuti Anggarawati; Erni Suprapti (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Pregnant will experience an increase in blood volume and this causes iron requirements to increase. Iron needs can be met by food consumed daily with the addition of iron supplements and if iron needs are not met it can cause anemia. Anemia in pregnant can increase the risk of premature birth, maternal and child death, and infectious diseases. Anemia can affect the growth and development of the fetus or baby during pregnancy or after. The government's efforts to prevent anemia include improving the quality of health services, financing health insurance, providing 90 blood supplement tablets during pregnancy, and health education about nutrition and preventing anemia. Increasing knowledge is urgently needed to strengthen awareness in increasing knowledge and behavior in preventing anemia in pregnant. One of the efforts made is health education activities regarding the prevention and early detection of anemia in pregnant. The result of this community service activity is that there is an increase in knowledge about anemia in pregnant before and after being given health education